2023
DOI: 10.1007/s00415-023-11682-6
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem–cortex disconnection in amyotrophic lateral sclerosis: bulbar impairment, genotype associations, asymptomatic changes and biomarker opportunities

Abstract: Background Bulbar dysfunction is a cardinal feature of ALS with important quality of life and management implications. The objective of this study is the longitudinal evaluation of a large panel imaging metrics pertaining to bulbar dysfunction, encompassing cortical measures, structural and functional cortico-medullary connectivity indices and brainstem metrics. Methods A standardised, multimodal imaging protocol was implemented with clinical and genetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The imaging studies of these 'early' PLS cohorts have revealed a pattern consistent with what is now called 'definite PLS' validating the utility of the new criteria [9,10]. Hereditary spastic paraparesis (HSP) has overlapping clinical features with PLS and the marked corticospinal, corpus callosum and, depending on genotype, cerebellar degeneration is also reminiscent of some of the radiological alterations observed in ALS [11,12,13 && ,14]. Low-incidence ALS mimics, such as postpolio syndrome, was traditionally associated with widespread cerebral disease, but recent imaging studies have highlighted the lack of atrophy both in supra-tentorial and infra-tentorial regions [15,16].…”
Section: Phenotypic Heterogeneitymentioning
confidence: 73%
“…The imaging studies of these 'early' PLS cohorts have revealed a pattern consistent with what is now called 'definite PLS' validating the utility of the new criteria [9,10]. Hereditary spastic paraparesis (HSP) has overlapping clinical features with PLS and the marked corticospinal, corpus callosum and, depending on genotype, cerebellar degeneration is also reminiscent of some of the radiological alterations observed in ALS [11,12,13 && ,14]. Low-incidence ALS mimics, such as postpolio syndrome, was traditionally associated with widespread cerebral disease, but recent imaging studies have highlighted the lack of atrophy both in supra-tentorial and infra-tentorial regions [15,16].…”
Section: Phenotypic Heterogeneitymentioning
confidence: 73%
“…This notion is supported by our findings of left hemispheric FC reduction between the endpoints of the frontal aslant track in cognitively unimpaired ALS patients, where traditional tractography did not detect white matter alterations. This demonstrates the benefit of evaluating a panel of structural and FC indices in motor neuron diseases as they may have divergent sensitivity to detect network degeneration (Abidi et al., 2021 , 2020 ; Meier et al., 2020 ; Tahedl, Tan, Chipika, et al., 2023 ; Tahedl, Tan, Shing, et al., 2023 ; Trojsi, Di Nardo, Caiazzo, et al., 2020 ). SC is typically appraised based on diffusion data sets, which have their own caveats particularly around regions of crossing fibers.…”
Section: Discussionmentioning
confidence: 98%
“…Our analyses highlight that focal structural changes alone do not account for clinical symptoms and instead of solely performing voxel‐wise analyses, the integrity of specific networks and tracts should be also evaluated (Bede, 2017 ; Tahedl, Tan, Chipika, et al., 2023 ). The shift from focality to circuitry has been repeatedly emphasized in ALS (Bak & Chandran, 2012 ; Bak et al., 2001 ; Grossman et al., 2008 ) and is consistent with the observation that specific neuropsychological functions are mediated by multisynaptic networks with distinct cortical and white matter components, many relayed through specific subcortical nuclei and sometimes modulated by cerebellar afferents (Bede et al., 2018 ; Bonelli & Cummings, 2007 ).…”
Section: Discussionmentioning
confidence: 99%